Low-temperature-resistant wear-resistant polyvinyl chloride wire and cable material and preparation method thereof
By adding a specific cold -resistant and wearer to the polyvinyl chloride wire cable material, the problem of hardening, brittleness and lack of abrasion resistance in low temperature environments in low temperature environment is solved. The abrasion performance extends the life of the cable.
Patent Information
- Application Number
- CN202411478421.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional polyvinyl chloride wire and cable materials are prone to harden and brittle in low temperature environments, resulting in reduced flexibility and insufficient wear resistance, which makes the problem of outer skin wear.
Using a low -temperature -resistant wear -resistant polyvinyl chloride wire cable material, a cold -resistant and wearable resistant in the formula, of which the cold resistant agent is polyolefin, which is made of polyether polyol and diisocyanate polymerization. 95 % nano -active calcium carbonate.
It significantly improves the low-temperature resistance and wear resistance of wire and cable materials, extends its service life, and maintains good physical properties under extremely cold conditions.
Smart Images

Figure BDA0005096699130000151 
Figure BDA0005096699130000161
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cable materials, and in particular to a low-temperature-resistant and wear-resistant polyvinyl chloride wire and cable material and a preparation method thereof. Background Art
[0002] At present, in the field of wire and cable materials, polyvinyl chloride wire and cable materials are widely used due to their good insulation performance, processing performance and cost advantages. The traditional preparation process of polyvinyl chloride wire and cable materials is usually to mix polyvinyl chloride resin powder with plasticizers, stabilizers, lubricants and other additives, and then make it through extrusion, granulation and other processes.
[0003] However, the polyvinyl chloride wire and cable materials prepared by this traditional process have the following disadvantages:
[0004] 1. Poor low temperature resistance: In low temperature environments, traditional polyvinyl chloride wire and cable materials tend to become hard and brittle, resulting in reduced flexibility of wires and cables, and may even cause cracking, affecting their normal use.
[0005] 2. Insufficient wear resistance: During use, wires and cables may be subjected to external forces such as friction and scratches. Traditional polyvinyl chloride wire and cable materials have poor wear resistance, which can easily cause wear on the outer sheath of wires and cables and reduce their service life. Summary of the invention
[0006] The object of the present invention is to provide a low-temperature resistant and wear-resistant polyvinyl chloride wire and cable material and a preparation method thereof, so as to solve the problems of poor low-temperature resistance and insufficient wear resistance of polyvinyl chloride wire and cable materials in the prior art.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] A low-temperature-resistant and wear-resistant polyvinyl chloride wire and cable material comprises the following components by weight: 175-200 parts of polyvinyl chloride resin powder, 140-150 parts of plasticizer, 20-30 parts of cold-resistant oil, 80-100 parts of mineral powder, 20-50 parts of calcium carbonate, 2-5 parts of lubricant, 15-20 parts of stabilizer, 8-20 parts of cold-resistant agent, 15-25 parts of modifier, 2-5 parts of colorant and 24-30 parts of wear-resistant agent; the cold-resistant agent is a polyolefin formed by polymerization of polyether polyol and diisocyanate, and comprises the following components by weight: 100 parts of polyether polyol, 50 parts of diisocyanate, 5 parts of initiator and 200 parts of solvent.
[0009] Preferably, the polyvinyl chloride resin powder is a resin powder having a K value of 70 and an average degree of polymerization of 1250 to 1350;
[0010] The plasticizer is a combination of at least two of dioctyl phthalate, diisononyl phthalate, dioctyl terephthalate, trioctyl trimellitate, chlorinated paraffin, and epoxidized soybean oil;
[0011] The cold-resistant oil is one or a combination of two of dioctyl adipate, dioctyl sebacate, and di(2-propylheptyl) adipate;
[0012] The mineral powder is calcium carbonate with an average particle size of ≤2.0um and a calcium content of ≥95%;
[0013] The anti-wear agent is nano-active calcium carbonate with a calcium content of ≥95%;
[0014] The lubricant is a combination of at least two of carboxylates, fatty acid salts, paraffin wax, polyethylene wax, oxidized polyethylene wax, stearates, and fatty acid amides;
[0015] The thermal stability time of the stabilizer under dynamic conditions of 180°C is ≥40min;
[0016] The modifier is one or two of chlorinated polyethylene, nitrile rubber, acrylic copolymer, ethylene vinyl acetate copolymer, ethylene-octene copolymer, ethylene-hexene copolymer, and ethylene-butene copolymer;
[0017] The initiator in the cold-resistant agent is isopropanol and the solvent is ethanol; the preparation method is as follows:
[0018] (1) Accurately weigh polyether polyol, diisocyanate, isopropanol and ethanol according to the formula ratio, add ethanol into the reaction vessel, and slowly add polyether polyol and diisocyanate under stirring to fully dissolve them;
[0019] (2) Initiation of polymerization: Control the temperature of the reaction container at 120°C, slowly add initiator isopropanol, the initiator initiates the polymerization reaction of polyether polyol and diisocyanate, and the reaction time is 30-35 minutes;
[0020] (3) Purification treatment: After the reaction is completed, the reaction product is poured into a large amount of polystyrene to precipitate the polymer, the polymer precipitate is collected by filtration, and the polymer precipitate is washed with 20 ml of ethanol to remove unreacted monomers and impurities; the washed polymer is dried at 35°C to obtain a cold-resistant agent. Preferably, the stabilizer is one of composite lead, barium zinc or calcium zinc; the preparation method of the wear-resistant agent is as follows:
[0021] 1) adding nano-scale calcium carbonate powder to a stearic acid solution, and stirring the solution evenly by mechanical stirring or ultrasonic dispersion to allow the stearic acid to fully contact the calcium carbonate particles;
[0022] 2) reacting at 60°C for 20 minutes to allow stearic acid to react on the surface of calcium carbonate;
[0023] 3) After the reaction is completed, filtering and washing are performed to remove the unabsorbed stearic acid solution;
[0024] 4) Drying the treated calcium carbonate to obtain nano-scale calcium carbonate whose surface is treated with stearic acid.
[0025] A method for preparing a low-temperature-resistant and wear-resistant polyvinyl chloride wire and cable material as described above comprises the following steps:
[0026] A. Add polyvinyl chloride resin powder, plasticizer, cold-resistant oil, mineral powder and calcium carbonate into a mixer according to the formula ratio and mix evenly;
[0027] B. Add stabilizer, cold-resistant agent and modifier to the materials mixed evenly in step A according to the formula ratio, and mix evenly again;
[0028] C. mixing the colorant and the wear-resistant agent with the mixed materials in step B;
[0029] D. Raise the temperature of each section of the granulator, and then granulate the material mixed evenly in step C.
[0030] Preferably, the mixer in step A is a SRL50011000-PVC high-speed mixer; the stirring time is 6 to 10 minutes, during which the temperature is controlled at 40-60° C. and the rotation speed is 150 r / min.
[0031] Preferably, the stabilizer, cold-resistant agent and modifier in step B are added and stirred for 2-4 minutes.
[0032] Preferably, the mixer in step A is allowed to idle for 1-2 minutes before adding materials for stirring; and the stabilizer, cold-resistant agent and modifier in step B are added and stirred for 3 minutes.
[0033] Preferably, in step C, the uniformly mixed material in step B is sent to a storage hopper in a granulator, and then a colorant and an anti-wear agent are added and stirred for 3 to 4 minutes.
[0034] Preferably, in step D, the temperature of each section of the granulator is increased, wherein the temperature of the feeding section is controlled to be 85°C to 100°C, the temperature of the plasticizing section of the granulator is controlled to be 105°C to 120°C, 110°C to 130°C and 120°C to 130°C respectively, and the temperature of the discharging section of the granulator is controlled to be 110°C to 100°C.
[0035] Preferably, the discharging speed and pelletizing speed in step D are controlled so that the plastic particles are cut into cylindrical particles with a length and width of 3 mm×4 mm; the discharging speed in step D is 3 kg / min.
[0036] In summary, the present invention adds a cold-resistant agent and a wear-resistant agent to the formula. The cold-resistant agent adopts a new type of high molecular polymer, and the wear-resistant agent adopts a special nano material, which is a nano active calcium carbonate with a calcium content of ≥95%; this specific material and its combination significantly improve the low temperature resistance of the wire and cable material of the present invention, and expand the application range of wires and cables. DETAILED DESCRIPTION
[0037] In order to explain the technical content, achieved objectives and effects of the present invention in detail, the following is an explanation in conjunction with the implementation modes, but it does not constitute a limitation on the protection scope of the present invention.
[0038] As described in the background art, traditional polyvinyl chloride wire and cable materials have insufficient low temperature resistance and wear resistance and cannot meet the use requirements in some special environments.
[0039] Therefore, the present invention develops a low-temperature-resistant and wear-resistant polyvinyl chloride wire and cable material and a preparation method thereof to solve this problem. After rigorous scientific exploration, cold-resistant agents and wear-resistant agents are added to the formula. Cold-resistant agents can effectively improve the low-temperature resistance of wire and cable materials, so that they can still maintain good flexibility in low-temperature environments; wear-resistant agents can significantly enhance the wear resistance of wire and cable materials and extend their service life. At the same time, a large number of experimental comparisons were carried out in the stage of screening cold-resistant agents and wear-resistant agents, and the performance of different types of additives in low-temperature environments and the effect of improving wear resistance were considered, and the cold-resistant agents and wear-resistant agents were determined.
[0040] Among them, the cold-resistant agent uses a new type of high-molecular polymer with excellent low-temperature resistance. This high-molecular polymer can maintain good elasticity and flexibility at low temperatures and will not become hard or brittle.
[0041] The anti-wear agent uses a special nano material, which is a nano active calcium carbonate with a calcium content of ≥95%, which has extremely high hardness and wear resistance. This nano material can be evenly dispersed in wire and cable materials to form a strong wear-resistant layer, which effectively resists external forces such as friction and scratches. For anti-wear agents, it may be difficult to solve the dispersibility problem of nano materials, or there is a lack of in-depth research on their application effects in polyvinyl chloride wire and cable materials, so their application in the prior art has not been seen. The present application successfully solves the dispersion problem of nano materials in polyvinyl chloride by adopting a specific surface treatment technology, thereby realizing their effective application in wire and cable materials.
[0042] Then, the proportion of each ingredient in the formula is further fine-tuned. Through continuous testing and analysis, the best proportion combination is found to achieve a balance between low temperature resistance and wear resistance of wire and cable materials.
[0043] In terms of processing technology, specific process steps are adopted, such as precise control of processing temperature, stirring speed and time, to ensure that the cold-resistant agent and wear-resistant agent can be evenly dispersed in the polyvinyl chloride matrix. This can avoid the situation where the local additive concentration is too high or too low, thereby ensuring the stable and consistent performance of the entire wire and cable material. At the same time, specific processing technology can also promote the interaction between the various components and improve the comprehensive performance of the material.
[0044] At the same time, during the preparation process, the order of adding each raw material and the processing temperature are strictly controlled to ensure that each component is fully mixed and reacted. Specifically, the raw materials such as polyvinyl chloride resin powder, plasticizer, cold-resistant oil, mineral powder, calcium carbonate, etc. are first mixed evenly, and then additives such as stabilizers, cold-resistant agents, and modifiers are added, and finally colorants and wear-resistant agents are added. In terms of processing temperature, according to the characteristics of different raw materials, the extrusion temperature and granulation temperature are reasonably controlled to ensure the stable performance of wire and cable materials.
[0045] Through the above configuration, the low-temperature resistance and wear-resistant polyvinyl chloride wire and cable material of the present invention is significantly improved; at the same time, it still maintains good flexibility at extremely low temperatures, and will not become hard or brittle, ensuring the electrical performance and service life of the wire and cable. Not only does it greatly enhance the wear resistance of the wire and cable material, it can effectively resist external forces such as friction and scratching, reduce the wear of the outer skin of the wire and cable, and extend its service life; at the same time, it maintains other excellent properties of the polyvinyl chloride wire and cable material: such as good insulation performance, flame retardant performance, etc.
[0046] The development of the technical solution of the present invention will provide more reliable protection for wires and cables used in low-temperature environments, extend their service life, and reduce maintenance costs. It can be widely used in the fields of electricity, communications, etc. in cold regions to meet the needs of different industries for high-performance wires and cables.
[0047] The invention provides a low-temperature-resistant and wear-resistant polyvinyl chloride wire and cable material, which comprises the following components in parts by weight: 175-200 parts of polyvinyl chloride resin powder, 140-150 parts of plasticizer, 20-30 parts of cold-resistant oil, 80-100 parts of mineral powder, 20-50 parts of calcium carbonate, 2-5 parts of lubricant, 15-20 parts of stabilizer, 8-20 parts of cold-resistant agent, 15-25 parts of modifier, 2-5 parts of colorant and 24-30 parts of wear-resistant agent; the cold-resistant agent is a polyolefin formed by polymerization of polyether polyol and diisocyanate, and the cold-resistant agent comprises the following components in parts by weight: 100 parts of polyether polyol, 50 parts of diisocyanate, 5 parts of initiator and 200 parts of solvent.
[0048] Specifically, the polyvinyl chloride resin powder is a resin powder with a K value of 70 and an average polymerization degree of 1250-1350; the plasticizer is a combination of at least two of dioctyl phthalate, diisononyl phthalate, dioctyl terephthalate, trioctyl trimellitate, chlorinated paraffin, and epoxidized soybean oil; the cold-resistant oil is one or a combination of two of dioctyl adipate, dioctyl sebacate, and di(2-propylheptyl) adipate; the mineral powder is calcium carbonate with an average particle size of ≤2.0um and a calcium content of ≥95%; the calcium carbonate is a nano-active Calcium carbonate; the lubricant is a combination of at least two of carboxylates, fatty acid salts, paraffin, polyethylene wax, oxidized polyethylene wax, stearates, and fatty acid amides; the stabilizer is one of composite lead, barium zinc, or calcium zinc, and the thermal stability time under dynamic conditions at 180°C is ≥40min; the modifier is one or two of chlorinated polyethylene, nitrile rubber, acrylic copolymer, ethylene vinyl acetate copolymer, ethylene-octene copolymer, ethylene-hexene copolymer, and ethylene-butene copolymer; the initiator in the cold-resistant agent is isopropanol, and the solvent is ethanol.
[0049] The preparation method of the cold-resistant agent in the present invention is as follows:
[0050] (1) The cold-resistant agent includes the following components by weight: 100 parts of polyether polyol, 50 parts of diisocyanate, 5 parts of isopropanol, and 200 parts of ethanol. To ensure the purity and accuracy of the raw materials, accurately weigh the polyether polyol, diisocyanate, isopropanol and ethanol according to the formula ratio, add ethanol to the reaction container, and slowly add the polyether polyol and diisocyanate under stirring to fully dissolve them;
[0051] (2) Initiation of polymerization: Control the temperature of the reaction container at 120°C, slowly add initiator isopropanol, the initiator initiates the polymerization reaction of polyether polyol and diisocyanate, the reaction time is 30-35 minutes, and the actual reaction time is adjusted according to the actual situation;
[0052] (3) Purification treatment: After the reaction is completed, the reaction product is poured into a large amount of polystyrene to precipitate the polymer, the polymer precipitate is collected by filtration, and the polymer precipitate is washed with 20 ml of ethanol to remove unreacted monomers and impurities; the washed polymer is dried at 35°C to obtain this new high molecular polymer product - the cold-resistant agent of the present invention.
[0053] The preparation method of the anti-wear agent in the present invention is as follows:
[0054] 1) dissolving stearic acid in an appropriate amount of solvent to prepare a stearic acid solution of a certain concentration; adding nano-scale calcium carbonate powder to the stearic acid solution, and stirring evenly by mechanical stirring or ultrasonic dispersion, so that the stearic acid is fully in contact with the calcium carbonate particles;
[0055] 2) reacting at 60°C for 20 minutes to allow stearic acid to react chemically on the surface of calcium carbonate;
[0056] 3) After the reaction is completed, filtering and washing are performed to remove the unabsorbed stearic acid and solvent;
[0057] 4) Drying the treated calcium carbonate to obtain nano-scale calcium carbonate whose surface is treated with stearic acid.
[0058] The dispersibility test method and results of the anti-wear agent in the present invention are as follows:
[0059] 1. Test Method
[0060] 1. Prepare polyvinyl chloride samples containing different proportions of wear-resistant agent nano-calcium carbonate.
[0061] 2. Use an optical microscope to observe the samples and record the dispersion of nano-calcium carbonate in polyvinyl chloride.
[0062] 3. Use scanning electron microscopy (SEM) to analyze the microstructure of the samples and measure the distribution uniformity of nano-calcium carbonate particles.
[0063] 4. The particle size distribution of nano calcium carbonate in the sample was measured by laser particle size analyzer to evaluate the dispersibility.
[0064] 2. Test Results
[0065] 1. Optical microscope observation:
[0066] When the content of nano calcium carbonate is 82%, a small amount of nano calcium carbonate particles can be observed to agglomerate in polyvinyl chloride, but most of the particles are dispersed more evenly. As the content of nano calcium carbonate increases to 90%, the agglomeration phenomenon increases slightly, but the overall dispersion is still good. When the content reaches 95%, obvious agglomeration areas appear, but some areas are still well dispersed.
[0067] 2.SEM analysis:
[0068] In the polyvinyl chloride samples with low content of nano-calcium carbonate, the nano-calcium carbonate particles are evenly distributed in the polyvinyl chloride matrix, and the distance between the particles is relatively uniform. In the samples with high content, nano-calcium carbonate particles are accumulated in some areas, but a good dispersion state can still be observed in other areas. Through measurement, the distribution uniformity of nano-calcium carbonate particles can reach 98% at low content, and gradually decreases to 95% as the content increases.
[0069] 3. Laser particle size analysis:
[0070] The particle size distribution of the polyvinyl chloride sample without the addition of nano calcium carbonate is relatively concentrated. After adding nano calcium carbonate, the particle size distribution range becomes wider, but with the application of surface treatment technology, the particle size distribution gradually stabilizes. When the nano calcium carbonate content is 85%, the average particle size is 1.8um; when the content is 90%, the average particle size is 1.9um; when the content is 95%, the average particle size is 2.0um.
[0071] Conclusion
[0072] From the above dispersibility test data, it can be seen that the wear-resistant agent nano calcium carbonate has good dispersibility in polyvinyl chloride. The specific surface treatment technology effectively reduces the agglomeration of nano calcium carbonate, allowing it to be evenly distributed in polyvinyl chloride. However, as the content of nano calcium carbonate increases, the dispersibility decreases slightly, but it is still within an acceptable range. In practical applications, the content of nano calcium carbonate can be adjusted according to specific needs to obtain the best performance.
[0073] Polyvinyl chloride resin powder has good insulation properties and is used in the manufacture of outer sheaths for wires and cables. The principle of polyvinyl chloride resin powder is that vinyl chloride monomer (VCM) is polymerized by adding various auxiliary materials in a polymerization kettle. The polymerization process can be carried out by emulsion polymerization, suspension polymerization, bulk polymerization or solution polymerization. During the polymerization process, various fillers, diluents, heat stabilizers, foaming agents and light stabilizers can be added according to different needs.
[0074] Polyvinyl chloride resin is a thermoplastic, and its performance is related to factors such as degree of polymerization and molecular weight. Generally speaking, polyvinyl chloride with a higher molecular weight has better physical properties, while polyvinyl chloride with a lower molecular weight has better processing properties.
[0075] Plasticizers can make plastic products softer, more flexible and easier to process, and improve their physical properties. They help reduce the melting temperature and viscosity of materials, making plastics easier to flow and form during processing. They can keep plastic products flexible and less prone to brittle cracks in low temperature environments. They help mix and compatibility between different plastic components, and improve the uniformity of materials. To a certain extent, they can reduce the amount of main plastic components used, thereby reducing production costs.
[0076] Cold-resistant oil makes the cable have excellent low-temperature performance, and it is also a long-lasting cold-resistant and antifreeze lubricating product; it also has excellent wear resistance, plastic and metal compatibility, and can be used safely and with confidence; it has excellent oxidation resistance, low oil diffusion and evaporation loss, and can effectively extend the service life; it has a small friction coefficient and strong load-bearing capacity, and can effectively resist wear, heavy loads and extreme pressure; it has excellent lubricity, does not contain silicon, and has no effect on electrical contacts; it has excellent water resistance and can maintain good lubrication in a water environment without emulsification or dilution. When using, be sure to ensure that the greased area is dry and clean, do not mix with other greases, and strictly prevent impurities from mixing during use and storage; due to the many types of plastics, special plastic parts should be tested for compatibility before use.
[0077] Mineral powder can improve rigidity and hardness. For example, calcium carbonate can improve the heat resistance and hardness of products. Talc is often used for PP filling and modification to improve rigidity, hardness or heat resistance; mica powder can increase the rigidity of materials; kaolin can improve the heat resistance and insulation properties of plastics. For example, the thermal conductivity of talc is higher than that of polymers. Its addition can effectively improve the thermal conductivity of plastics, thereby improving production efficiency. A trace amount of fine talc can improve the crystallinity of polypropylene, similar to the role of nucleating agents. It keeps plastics rigid at high temperatures. Compared with unfilled polymers, the creep of polymers filled with talc is significantly reduced. It is helpful for applications in food packaging and other fields. Although mineral filling does not usually improve impact strength, in certain specific applications, such as PP composite materials for car bumpers, adding fine-particle talc can improve impact strength. Mineral powders with different particle morphologies have different effects on the performance of plastic products. For example, granular powder particles (such as heavy calcium carbonate) can improve the rigidity and impact resistance of the material to a certain extent; fibrous particles (such as wollastonite) can greatly improve the bending modulus; plate-like particles (such as talc) can significantly improve the bending modulus. Some mineral powders can be used to adjust the color and opacity of plastic products.
[0078] Calcium carbonate exists in large quantities in nature and is easy to obtain, making it relatively cheap. It can effectively increase the volume of products and reduce production costs. For example, in plastics, rubber and other products, it enhances their mechanical properties. It helps to improve the stability of products in high temperature environments. It is non-toxic, harmless and relatively friendly to the environment.
[0079] Lubricants can significantly reduce the friction between surfaces in contact with each other, extend the service life of mechanical equipment, and reduce the damage and replacement frequency of parts. They can reduce energy loss caused by friction, improve the operating efficiency of mechanical systems, and save energy. They can reduce frictional heat, prevent parts from failing due to overheating, and help maintain the normal operating temperature of equipment. They can make moving parts run more smoothly, reduce noise levels, and improve the comfort of the working environment. They can form a protective film on the metal surface, isolate air and moisture, and reduce the occurrence of corrosion and rust. They can provide good lubrication between seals and contact surfaces, improve sealing effects, and prevent leakage.
[0080] Stabilizers can effectively prevent materials from undergoing adverse changes such as degradation, discoloration, and loss of physical properties during processing, storage, and use, and maintain the original performance and quality of the materials. By inhibiting chemical reactions and physical changes, the service life of the product can be extended and maintenance and replacement costs can be reduced. It helps materials maintain good fluidity and processability under processing conditions such as high temperature and high pressure, and improves production efficiency and product quality. It enhances the material's resistance to environmental factors (such as ultraviolet rays, oxygen, humidity, etc.) so that it can be used stably for a long time outdoors or in harsh environments. It prevents materials from changing color, fading, or having a rough surface due to aging or chemical reactions, and maintains the aesthetics of the product. For some application scenarios (such as the insulation layer of wires and cables), stabilizers can ensure the safety and reliability of the material during use.
[0081] Cold-resistant agents can significantly improve the flexibility, elasticity and impact resistance of materials in low-temperature environments, and prevent materials from becoming brittle and cracking under cold conditions. It enables materials that are not cold-resistant to be used normally in cold areas or low-temperature working conditions, expanding the application field of the product. While enhancing cold resistance, it minimizes the adverse effects on other important physical properties of the material (such as strength, hardness, etc.). It reduces the damage of low temperature to materials, thereby extending the service life of products in cold environments. It ensures the stable operation and performance of products under low-temperature conditions, and enhances the reliability of systems or equipment. Since the material has stable performance at low temperatures, the maintenance and replacement costs caused by low-temperature damage are reduced. It helps products work normally in extremely cold climates and meet the needs of special environments.
[0082] Modifiers can significantly improve the physical, chemical or mechanical properties of materials, such as strength, toughness, wear resistance, corrosion resistance, etc., making them more suitable for specific application requirements. They help improve the quality and stability of products and reduce defective rates and quality fluctuations. They give materials new functional properties, such as electrical conductivity, thermal conductivity, flame retardancy, etc., to expand the application areas of materials. They make materials easier to form, extrude, and inject during processing, improve production efficiency and reduce processing costs. They promote mixing and compatibility between different materials and improve the comprehensive properties of composite materials. They enhance the resistance of materials to environmental factors (such as temperature, humidity, ultraviolet rays, etc.) and extend their service life. By optimizing material properties, the use of expensive raw materials can be reduced to a certain extent, or cheaper alternative materials can be used, thereby reducing production costs. They provide possibilities for product innovation, enabling companies to develop products with unique properties and competitive advantages and stand out in the market.
[0083] A method for preparing low-temperature-resistant and wear-resistant polyvinyl chloride wire and cable material, the steps of which are as follows:
[0084] A. Add polyvinyl chloride resin powder, plasticizer, cold-resistant oil, mineral powder and calcium carbonate into a high-speed mixer.
[0085] After mixing evenly, stir at high speed for 6 to 10 minutes. The mixer uses SRL50011000-PVC high-speed mixer. Before adding materials for stirring, let the mixer run idle for 1 to 2 minutes.
[0086] During mixing, the temperature in the mixer should be controlled within an appropriate range, generally maintained at 40-60°C;
[0087] B. Add stabilizer, cold-resistant agent and modifier to the mixed materials in step A, mix them evenly again, and stir for 2 to 3 minutes;
[0088] C. Send the mixed material in step B to the storage hopper in the granulator, add the colorant and the wear-resistant agent and mix them evenly, and stir for 3 to 4 minutes to prepare for granulation;
[0089] D. Raise the temperature of each section of the granulator, control the temperature of the feeding section to 85℃~100℃, the temperature of the plasticizing section of the granulator to 105℃~120℃, 110℃~130℃ and 120~130℃ respectively, and the temperature of the discharging section of the granulator to 110℃~100℃; control the discharging speed and pelletizing speed in step D so that the length and width of the plastic pellets are cut to 3mm
[0090] ×4mm cylindrical particles; the discharge rate is 3kg / min.
[0091] The low-temperature-resistant and wear-resistant polyvinyl chloride wire and cable material of the present invention can withstand low-temperature embrittlement impact of -25 to -50°C, so that the extruded wire and cable can be used in a cold low-temperature environment of -25 to -45°C without the risk of embrittlement and cracking.
[0092] After rigorous testing, the impact strength of the wire and cable material of the present invention can reach 1.8 joules / square centimeter at -25°C, which is 85% higher than that of traditional polyvinyl chloride wire and cable materials. In an environment of -30°C, the elongation at break of the material can still be maintained at more than 92%, showing excellent flexibility. When the temperature drops to -40°C, the hardness of the material is only 100P, indicating that it can still maintain good physical properties under extremely cold conditions. At the extreme low temperature of -50°C, the wire and cable material is subjected to a brittle impact test, and its passing probability is as high as 98%, which is much higher than the industry standard requirements.
[0093] In actual applications, the extruded wires and cables were monitored for a long time in a cold low-temperature environment of -25℃ to -45℃. After 2 hours of continuous operation, no signs of brittle cracking were found. Multiple groups of samples were subjected to repeated bending, stretching and other mechanical property tests. The results showed that within this temperature range, the performance indicators of the wires and cables can meet the use requirements, and the performance decay is very slow. For example, in a bending test at -45℃, the minimum bending radius that the wires and cables can withstand is only 12 mm higher than that at room temperature, which fully proves its reliability and stability in cold low-temperature environments.
[0094] The glass transition temperature refers to the temperature at which amorphous polymers (including the amorphous part of crystalline polymers) transform between the glass state and the rubber state. For polyolefin binary copolymers modified by micro-crosslinking, the glass transition temperature reflects the performance changes of the material at low temperatures. When the temperature is lower than Tg, the material is in the glass state, the movement of molecular chains and segments is restricted, the material becomes hard and brittle, and the elasticity and flexibility are poor; when the temperature is higher than Tg, the molecular segments begin to move, and the material exhibits high elasticity.
[0095] Tg is an important characteristic temperature of polymers, which has a great influence on the operating temperature range and performance of materials. Polymers with lower Tg can usually maintain a certain degree of flexibility and elasticity in low temperature environments, that is, they have better cold resistance. By adjusting the Tg of polyolefin binary copolymers through micro-crosslinking modification, it can have more ideal performance within a specific temperature range.
[0096] Cross-linking temperature refers to the temperature required for the cross-linking reaction. Cross-linking can increase the molecular weight of the polymer, improve its strength, heat resistance, chemical corrosion resistance and other properties. For polyolefin binary copolymers modified by micro-cross-linking, selecting a suitable cross-linking temperature can ensure the effective cross-linking reaction, thereby achieving the desired modification effect.
[0097] The present invention is further described in detail below in conjunction with specific embodiments.
[0098] Embodiment 1:
[0099] A low-temperature-resistant and wear-resistant polyvinyl chloride wire and cable material is composed of the following raw materials by weight: 180 grams of polyvinyl chloride resin powder, 140 grams of plasticizer, 20 grams of cold-resistant oil, 80 grams of mineral powder, 20 grams of calcium carbonate, 2 grams of lubricant, 15 grams of stabilizer, 8 grams of cold-resistant agent, 10 grams of modifier, 2 grams of colorant, and 24 grams of wear-resistant agent.
[0100] The preparation method is as follows:
[0101] A. Add polyvinyl chloride resin powder, plasticizer, cold-resistant oil, mineral powder and calcium carbonate into a high-speed mixer. After mixing evenly, stir at high speed for 6 to 10 minutes. The mixer uses SRL50011000-PVC high-speed mixer. Before adding materials for stirring, let the mixer run idle for 1 to 2 minutes. Stirring process
[0102] During mixing, the temperature in the mixer should be controlled within an appropriate range, generally maintained at 40-60°C;
[0103] B. Add stabilizer, cold-resistant agent and modifier to the mixed materials in step A, mix them evenly again, and stir for 2 to 3 minutes;
[0104] C. Send the mixed material in step B to the storage hopper in the granulator, add the colorant and the wear-resistant agent and mix them evenly, and stir for 3 to 4 minutes to prepare for granulation;
[0105] D. Raise the temperature of each section of the granulator, control the temperature of the feeding section to 85℃~100℃, the temperature of the plasticizing section of the granulator to 105℃~120℃, 110℃~130℃ and 120~130℃ respectively, and the temperature of the discharging section of the granulator to 110℃~100℃; control the discharging speed and pelletizing speed in step D so that the length and width of the plastic pellets are cut to 3mm
[0106] ×4mm cylindrical particles; the discharge rate is 3kg / min.
[0107] Embodiment 2:
[0108] A low-temperature-resistant and wear-resistant polyvinyl chloride wire and cable material is composed of the following raw materials by weight: 200 grams of polyvinyl chloride resin powder, 150 grams of plasticizer, 30 grams of cold-resistant oil, 100 grams of mineral powder, 50 grams of calcium carbonate, 5 grams of lubricant, 20 grams of stabilizer, 15 grams of cold-resistant agent, 20 grams of modifier, 5 grams of colorant, and 30 grams of wear-resistant agent.
[0109] The preparation method is the same as that in Example 1.
[0110] Embodiment 3:
[0111] A low-temperature-resistant and wear-resistant polyvinyl chloride wire and cable material is composed of the following raw materials by weight: 175 grams of polyvinyl chloride resin powder, 150 grams of plasticizer, 25 grams of cold-resistant oil, 90 grams of mineral powder, 55 grams of calcium carbonate, 3 grams of lubricant, 18 grams of stabilizer, 16 grams of cold-resistant agent, 21 grams of modifier, 4 grams of colorant, and 30 grams of wear-resistant agent.
[0112] The preparation method is the same as that in Example 1.
[0113] Embodiment 4:
[0114] A low-temperature and wear-resistant polyvinyl chloride wire and cable material is composed of the following raw materials by weight: 185 grams of polyvinyl chloride resin powder, 145 grams of plasticizer, 30 grams of cold-resistant oil, 95 grams of mineral powder, 45 grams of calcium carbonate, 4 grams of lubricant, 20 grams of stabilizer, 20 grams of cold-resistant agent, 20 grams of modifier, 5 grams of colorant, and 25 grams of wear-resistant agent.
[0115] The preparation method is the same as that in Example 1.
[0116] The following table shows the specific material types used in the components of the embodiments of the present invention:
[0117] Material Name model Manufacturer Polyvinyl chloride resin powder SG-5 Tianjin Yunkai Resin Technology Co., Ltd. Plasticizer DBP Wuxi Binwang Chemical Factory Cold resistant oil DOA Hubei Zhenzhengfeng New Materials Co., Ltd. Mineral powder <![CDATA[Al2Si2O5(OH)4]]> Suzhou Dongbai Chemical Co., Ltd. Calcium carbonate GCC-Ground Calcium Carbonate Tiantai High-tech (Guangzhou) Co., Ltd. Lubricants PE-WM-20 Foshan Hantu Environmental Protection Technology Co., Ltd. Stabilizer DOTMA-8 Guangzhou Jingyi New Materials Co., Ltd. Modifier PPN-M Shanghai Linden Information Technology Co., Ltd. Colorants PB-Pht Jiangsu Haipu Functional Materials Co., Ltd.
[0118] The preparation method of the cold-resistant agent of the embodiment of the present invention is as follows:
[0119] (1) The cold-resistant agent includes the following components by weight: 100 parts of polyether polyol, 50 parts of diisocyanate, 5 parts of isopropanol, and 200 parts of ethanol. To ensure the purity and accuracy of the raw materials, accurately weigh the polyether polyol, diisocyanate, isopropanol and ethanol according to the formula ratio, add ethanol to the reaction container, and slowly add the polyether polyol and diisocyanate under stirring to fully dissolve them;
[0120] (2) Initiation of polymerization: Control the temperature of the reaction container at 120°C, slowly add initiator isopropanol, the initiator initiates the polymerization reaction of polyether polyol and diisocyanate, the reaction time is 30-35 minutes, and the actual reaction time is adjusted according to the actual situation;
[0121] (3) Purification treatment: After the reaction is completed, the reaction product is poured into a large amount of polystyrene to precipitate the polymer, the polymer precipitate is collected by filtration, and the polymer precipitate is washed with 20 ml of ethanol to remove unreacted monomers and impurities; the washed polymer is dried at 35°C to obtain this new high molecular polymer product - the cold-resistant agent of the present invention.
[0122] The preparation method of the wear-resistant agent of the embodiment of the present invention is as follows:
[0123] 1) dissolving stearic acid in an appropriate amount of solvent to prepare a stearic acid solution of a certain concentration; adding nano-scale calcium carbonate powder to the stearic acid solution, and stirring evenly by mechanical stirring or ultrasonic dispersion, so that the stearic acid is fully in contact with the calcium carbonate particles;
[0124] 2) reacting at 60°C for 20 minutes to allow stearic acid to react chemically on the surface of calcium carbonate;
[0125] 3) After the reaction is completed, filtering and washing are performed to remove the unabsorbed stearic acid and solvent;
[0126] 4) Drying the treated calcium carbonate to obtain nano-scale calcium carbonate whose surface is treated with stearic acid.
[0127] The components of the embodiments are summarized in the table below:
[0128]
[0129] The polyvinyl chloride resin powder in the above table has a K value of 70 and an average degree of polymerization of 1250-1350. The plasticizer is dioctyl phthalate. The mineral powder is calcium carbonate with an average particle size of 1um and a calcium content of 95%. The anti-wear agent is nano-grade, surface treated with stearic acid or olive oil, and is a nano-active calcium carbonate with a calcium content of 95.5%. The lubricant is alcohol ether carboxylate (AEC), such as alcohol ether carboxylate AEC-9NA, which has the characteristics of acid and alkali resistance, hard water resistance and solubilization. It is widely used in formulations such as cleaning agents and emulsifiers, and can effectively improve the cleaning effect and stability of the product. The stabilizer uses composite lead, and the thermal stability time under dynamic conditions of 180°C is ≥40min.
[0130] Comparative verification: In order to verify the performance of the low-temperature and wear-resistant polyvinyl chloride wire and cable materials (Examples 1-4) of the present invention, the performance tests were carried out on the embodiments (1-4) and the currently sold wire and cable materials (the product name is low-temperature and wear-resistant polyvinyl chloride wire materials), and the currently sold wire and cable materials were used as comparison examples.
[0131] The test measures oxygen index (testing oxygen index of flame-retardant cable materials at room temperature by GB / T2406 method), tensile strength, elongation at break, electrical properties (testing tensile strength, elongation at break, electrical properties before and after aging by GB / T5023), and wear resistance (testing by enterprise standard Q / SJLY008). Through this test, it is proved that the low-temperature and wear-resistant polyvinyl chloride wire and cable material of the present invention performs well in low-temperature resistance and wear resistance, and has good electrical and mechanical properties. The material is expected to play an important role in wire and cable applications in low-temperature environments and high-wear conditions.
[0132] The detection performance is shown in the table below:
[0133]
[0134] At the same time, in order to verify the performance of the low temperature and wear resistant polyvinyl chloride wire and cable material of the present invention, the following experiments were carried out:
[0135] 1. Low temperature resistance test:
[0136] The comparative example and the wire and cable materials of the present invention were made into standard samples, placed in a low temperature box, and tested at different temperatures. The results showed that the comparative example began to harden and become brittle at -20°C, while the wire and cable materials of the present invention still maintained good flexibility at -40°C.
[0137] 2. Wear resistance test:
[0138] The wear resistance of the comparative example and the wire and cable material of the present invention was tested using a friction and wear tester. The results showed that the wear amount of the comparative example was 100 mg, while the wear amount of the wire and cable material of the present invention was only 50 mg.
[0139] Analysis and summary: It can be seen from the experimental data that the performance of Examples 1 to 4 meets the requirements of low temperature resistant and wear resistant polyvinyl chloride wire and cable materials, among which Example 1 shows more superior performance. They are superior in low temperature resistance and wear resistance, meet the standards of this type of wire and cable materials, meet the requirements of low temperature resistance and wear resistance, and show superiority compared with the comparative example. The specific analysis is as follows:
[0140] 1. From the perspective of low temperature resistance:
[0141] Example 1 was subjected to embrittlement impact test at a low temperature of -50°C, and the impact strength reached 1.8 joules / square centimeter, and no embrittlement cracking occurred. In contrast, the comparative example began to show obvious signs of embrittlement at -30°C, and the impact strength was only 1.6 joules / square centimeter. At a low temperature of -45°C, the elongation at break of Example 1 remained at 95%, while the elongation at break of the ordinary material was only 60%.
[0142] In the brittle impact test of Example 2-4 at a low temperature of -50°C, the impact strength can only reach 1.2 joules / cm2, and brittle cracking occurs. At a low temperature of -45°C, the elongation at break of Example 2-4 is 65%.
[0143] 2. Wear resistance:
[0144] After a specific wear test, the wear rate of Example 1 is 80%, and the surface hardness is moderate, which is 100P. The wear rate of ordinary materials is as high as 60%, and the surface hardness is either too high to cause insufficient flexibility, or too low to cause poor wear resistance.
[0145] The wear rate of Example 2-4 is 65%, and the surface hardness is moderate, which is 60P.
[0146] Example 1 is analyzed from the application scenario, as follows:
[0147] 1. Low temperature resistance:
[0148] Embodiment 1 can maintain good performance at lower temperatures, greatly expanding the application scope of wires and cables, especially in the fields of electricity and communications in extremely cold regions. For example, in cold northern regions or high-altitude areas, ordinary wires and cables may become brittle and crack due to low temperatures, resulting in power transmission interruption or communication failure, while Embodiment 1 can ensure stable operation in these harsh environments.
[0149] High elongation at break means that the cable still has good flexibility at low temperatures and can withstand certain external forces without breaking. This is very important for the bending and stretching of wires and cables during installation and use, and can reduce the risk of damage caused by low temperatures.
[0150] 2. Wear resistance:
[0151] The lower wear rate indicates that Example 1 has better wear resistance and can extend the service life of wires and cables. In some special application scenarios, such as industrial production environments, wires and cables may be subjected to external forces such as friction and scratching. Example 1 can better resist such wear and tear and reduce maintenance and replacement costs.
[0152] Moderate surface hardness ensures wear resistance without affecting the flexibility and installation convenience of wires and cables. In contrast, the uneven surface hardness of ordinary materials may cause various problems in actual use, such as easy breakage due to being too hard and easy wear due to being too soft.
[0153] In summary, it can be clearly seen from the comparison of experimental data that the low temperature and wear resistant polyvinyl chloride wire and cable material of Example 1 fully meets the industry requirements, and shows significant superiority in low temperature resistance and wear resistance, and has broad market application prospects. The low temperature and wear resistant polyvinyl chloride wire and cable material of the present invention is significantly better than the comparative example in terms of low temperature resistance and wear resistance. This shows that the formula and preparation method adopted by the present invention can effectively improve the performance of wire and cable materials and meet the use requirements under special environments.
[0154] The above embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A low temperature resistant and wear resistant polyvinyl chloride wire and cable material, characterized in that: The invention comprises the following components in parts by weight: 175-200 parts of polyvinyl chloride resin powder, 140-150 parts of plasticizer, 20-30 parts of cold-resistant oil, 80-100 parts of mineral powder, 20-50 parts of calcium carbonate, 2-5 parts of lubricant, 15-20 parts of stabilizer, 8-20 parts of cold-resistant agent, 15-25 parts of modifier, 2-5 parts of colorant and 24-30 parts of wear-resistant agent; the cold-resistant agent is a polyolefin formed by polymerization of polyether polyol and diisocyanate, and the cold-resistant agent comprises the following components in parts by weight: 100 parts of polyether polyol, 50 parts of diisocyanate, 5 parts of initiator and 200 parts of solvent.
2. The low temperature and wear resistant polyvinyl chloride wire and cable material according to claim 1, characterized in that: The polyvinyl chloride resin powder is a resin powder with a K value of 70 and an average degree of polymerization of 1250 to 1350; The plasticizer is a combination of at least two of dioctyl phthalate, diisononyl phthalate, dioctyl terephthalate, trioctyl trimellitate, chlorinated paraffin, and epoxidized soybean oil; The cold-resistant oil is one or a combination of two of dioctyl adipate, dioctyl sebacate, and di(2-propylheptyl) adipate; The mineral powder is calcium carbonate with an average particle size of ≤2.0um and a calcium content of ≥95%; The anti-wear agent is nano-active calcium carbonate with a calcium content of ≥95%; The lubricant is a combination of at least two of carboxylates, fatty acid salts, paraffin wax, polyethylene wax, oxidized polyethylene wax, stearates, and fatty acid amides; The thermal stability time of the stabilizer under dynamic conditions of 180°C is ≥40min; The modifier is one or two of chlorinated polyethylene, nitrile rubber, acrylic copolymer, ethylene vinyl acetate copolymer, ethylene-octene copolymer, ethylene-hexene copolymer, and ethylene-butene copolymer; The initiator in the cold-resistant agent is isopropanol and the solvent is ethanol; the preparation method is as follows: (1) Accurately weigh polyether polyol, diisocyanate, isopropanol and ethanol according to the formula ratio, add ethanol into the reaction vessel, and slowly add polyether polyol and diisocyanate under stirring to fully dissolve them; (2) Initiation of polymerization: Control the temperature of the reaction container at 120°C, slowly add initiator isopropanol, the initiator initiates the polymerization reaction of polyether polyol and diisocyanate, and the reaction time is 30-35 minutes; (3) Purification treatment: After the reaction is completed, the reaction product is poured into a large amount of polystyrene to precipitate the polymer, the polymer precipitate is collected by filtration, and the polymer precipitate is washed with 20 ml of ethanol to remove unreacted monomers and impurities; the washed polymer is dried at 35°C to obtain a cold-resistant agent.
3. The low temperature resistant and wear resistant polyvinyl chloride wire and cable material according to claim 2, characterized in that: The stabilizer is one of composite lead, barium zinc or calcium zinc; The preparation method of the wear-resistant agent is as follows: 1) adding nano-scale calcium carbonate powder to a stearic acid solution, and stirring the solution evenly by mechanical stirring or ultrasonic dispersion to allow the stearic acid to fully contact the calcium carbonate particles; 2) reacting at 60°C for 20 minutes to allow stearic acid to react on the surface of calcium carbonate; 3) After the reaction is completed, filtering and washing are performed to remove the unabsorbed stearic acid solution; 4) Drying the treated calcium carbonate to obtain nano-scale calcium carbonate whose surface is treated with stearic acid.
4. A method for preparing a low-temperature-resistant and wear-resistant polyvinyl chloride wire and cable material as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: A. Add polyvinyl chloride resin powder, plasticizer, cold-resistant oil, mineral powder and calcium carbonate into a mixer according to the formula ratio and mix evenly; B. Add stabilizer, cold-resistant agent and modifier to the materials mixed evenly in step A according to the formula ratio, and mix evenly again; C. mixing the colorant and the wear-resistant agent evenly with the mixed materials in step B; D. Raise the temperature of each section of the granulator, and then granulate the material mixed evenly in step C.
5. The method for preparing a low-temperature-resistant and wear-resistant polyvinyl chloride wire and cable material according to claim 4, characterized in that: The mixer in step A is a SRL50011000-PVC high-speed mixer; the stirring time is 6 to 10 minutes, during which the temperature is controlled at 40-60° C. and the rotation speed is 150 r / min.
6. The method for preparing a low-temperature-resistant and wear-resistant polyvinyl chloride wire and cable material according to claim 5, characterized in that: After adding the stabilizer, cold-resistant agent and modifier in step B, stirring is continued for 2-4 minutes.
7. The method for preparing a low temperature resistant and wear resistant polyvinyl chloride wire and cable material according to claim 6, characterized in that: Before adding materials to the mixer in step A for stirring, the mixer is allowed to idle for 1-2 minutes; after adding the modifier in step B, stirring is continued for 3 minutes.
8. The method for preparing a low temperature resistant and wear resistant polyvinyl chloride wire and cable material according to any one of claims 4 to 7, characterized in that: In the step C, the uniformly mixed materials in the step B are sent to the storage hopper in the granulator, and then the colorant and the wear-resistant agent are added and stirred for 3 to 4 minutes.
9. The method for preparing a low-temperature-resistant and wear-resistant polyvinyl chloride wire and cable material according to claim 8, characterized in that: In the step D, the temperature of each section of the granulator is increased, wherein the temperature of the feeding section is controlled to be 85°C to 100°C, the temperature of the plasticizing section of the granulator is controlled to be 105°C to 120°C, 110°C to 130°C and 120°C to 130°C respectively, and the temperature of the discharging section of the granulator is controlled to be 110°C to 100°C.
10. The method for preparing a low temperature resistant and wear resistant polyvinyl chloride wire and cable material according to claim 9, characterized in that: The discharging speed and pelletizing speed in step D are controlled so that the plastic particles are cut into cylindrical particles with a length and width of 3 mm×4 mm; the discharging speed in step D is 3 kg / min.
Citation Information
Patent Citations
Preparation method for antiflaming matt face wire and cable polyvinyl chloride colloidal particles
CN106188943A
Cold-resistant and heat-resistant polyvinyl chloride composite material and preparation method thereof
CN113185790A